2023
DOI: 10.1039/d3ra00454f
|View full text |Cite
|
Sign up to set email alerts
|

Emilia sonchifolia leaf extract-mediated green synthesis, characterization, in vitro biological activities, photocatalytic degradation and in vivo Danio rerio embryo toxicity of copper nanoparticles

Vainath Praveen Sankara Narayanan,
Sabeena Gabrial Kathirason,
Pushpalakshmi Elango
et al.

Abstract: Green-synthesised Cu nanoparticles were examined, and investigations were conducted on the photocatalytic activity of the nanoparticles for the degradation of methylene blue. The Cu nanoparticles were determined in vitro and in vivo biological activities to be significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Figure 2d shows the FT-IR spectra of biosynthesized AM-CuNPs and the A. monanthum extract. The FT-IR spectrum results revealed broadband peaks in the 3400-2400 cm −1 a b d c 220) and (222) planes, respectively, which are a perfect match with copper NPs [29]. In addition, the sharp intense peaks strongly supported the formation of copper NPs with an extremely crystalline nature, having values similar to the fcc cubic phases.…”
Section: Ft-ir Spectra Of Biosynthesized Am-cunpsmentioning
confidence: 79%
See 1 more Smart Citation
“…Figure 2d shows the FT-IR spectra of biosynthesized AM-CuNPs and the A. monanthum extract. The FT-IR spectrum results revealed broadband peaks in the 3400-2400 cm −1 a b d c 220) and (222) planes, respectively, which are a perfect match with copper NPs [29]. In addition, the sharp intense peaks strongly supported the formation of copper NPs with an extremely crystalline nature, having values similar to the fcc cubic phases.…”
Section: Ft-ir Spectra Of Biosynthesized Am-cunpsmentioning
confidence: 79%
“…Hence, the peak positions were consistent with the metallic copper of a crystalline nature reported earlier. Recently, Narayanan et al reported strong peaks at 2θ = 32.1 • , 35.2 • , 39.5 • , 49.5 • , 53.2 • , 62.3 • , 67.2 • , 68.5 • and 75.2 • , corresponding to the (100), (002), (111), (202), (020), (113), (311), (220) and (222) planes, respectively, which are a perfect match with copper NPs[29]. In addition, the sharp intense peaks strongly supported the formation of copper NPs with an extremely crystalline nature, having values similar to the fcc cubic phases.…”
mentioning
confidence: 99%